Epidemiological and pathological characteristics of Cutaneous Leishmaniasis from Baluchistan Province of Pakistan - Khan, Aisha; Sajid, Rawan; Gul, Shaista; Hussain, Ashiq; Zehri, Mohammad Tahir; Naz, Shumaila; Ahmed, Haroon (Cambridge Univ Press, 2021)
Cutaneous Leishmaniasis (CL) is considered a neglected tropical disease which in Pakistan can now be considered as a growing public health problem. The exact figures on the magnitude of the disease are lacking both at the national and regional level and only a few health centres are available for diagnosis of CL. The present study was designed to identify the epidemiology of CL infection from August 2018 to December 2019 and to assess clinical aspects of CL in Baluchistan Province of Pakistan. A total of 4072 clinically suspected CL cases were analysed statistically. The highest number of CL cases were reported in May, followed by April, January and then July, February and June and the lowest number of cases were observed in March and November. The highest prevalence rate was found in males where 38% of reported cases were aged 0-9 years. The majority (24.4%) of lesions were found on the hands followed by the face in which cheeks, ears and nose were the effected organs. About 50% of the participants have single lesion while 14% of the participants had two and nearly 3% of the participants have six lesions. The atypical clinical presentations were observed in Baluchistan and common unusual presentations were lupus erythematosus. The study findings suggest that more epidemiological studies and health education campaigns are needed for the population awareness regarding CL in Baluchistan. It is recommended that risk factors should be evaluated to establish control and management strategies to prevent disease at the individual and community level.
Keywords: Clinical features; Cutaneous Leishmaniasis; Leishmania tropica; Pakistan